NF-κB signaling pathway in osteosarcoma: from signaling networks to targeted therapy - Xue, Juandi; Yang, Xiao-ran; Wang, Li (Frontiers in Oncology, 2025)
Osteosarcoma (OS) is the most common primary malignant bone tumor that frequently occurs in children and adolescents. Although neoadjuvant chemotherapy has shown efficacy for OS, the long-term survival rate of OS patients remains low, highlighting the necessity of seeking more effective treatment methods. In cancer cells, abnormal activation of signaling pathways can widely affect cell activity from growth and proliferation to apoptosis, invasion and metastasis. As a highly complex and unique signal transduction pathway, the NF-κB pathway is involved in various physiological and pathological processes. In the field of oncology, the abnormal activation of the NF-κB pathway is closely related to the occurrence, development, metastasis and drug resistance of tumors, and is regarded as an important potential target for tumor treatment. Studies have confirmed that the NF-κB signaling pathway is an important driver of osteosarcoma. Abnormal activation of this pathway can promote the proliferation of osteosarcoma cells, inhibit apoptosis, enhance migration and invasion abilities, and immune escape processes. While inhibition of NF-κB pathway can effectively inhibit or reverse the above pathological processes. In this review, we summarized the role and mechanism of the NF-κB pathway in OS, discussed the therapeutic significance of targeting this pathway for OS, as well as the current insufficient research and problems to be solved regarding this pathway in OS. This review is helpful for us to understand the role of NF-κB on OS, and provides a theoretical basis for targeting the NF-κB pathway as a therapeutic target for OS and developing new therapeutic strategies.